IMPORTANT FACTORS ON SIDEWALKS WITH VENDOR ACTIVITIES BASED ON PEDESTRIAN PERCEPTION BY GENDER AND AGE - Hidayat, Nursyamsu; Choocharukul, Kasem; Kishi, Kunihiro (Jurnal Transportasi, 2012)
This paper presents an investigation of important factors relating sidewalk performance based on pedestrian perceptions by gender and age. Exploratory factor analysis technique and reliability test of the variables are performed on 45 items of sidewalk current condition in order to extract dimensions of pedestrian perceptions in Jakarta and Bangkok. Based on age, male respondents reveals that eight factors are identified as important on sidewalk performance, and labeled on the basis of the attributed covered as sidewalk interaction, comfort, space availability, safety, vendor problems, walking path, vendor regulation, and vendorâs attraction. On the other hand, the first seven factors are similarly stated by female respondents. Grouped by age, young respondents reveal nine factors are considered important and arbitrarily named as comfort, sidewalk interaction, safety, vendorâs attraction, vendor problems, vendor regulation, walking path, space availability, and sidewalk condition. The presence of vendors are often deemed as obstruction for walking flow, but their activities should be accommodated by establishing policies and management to accept high performance of the sidewalks and to support the cityâs economy.Keywords: sidewalk, street vendor, factor analysis